2022
DOI: 10.1186/s12915-022-01441-w
|View full text |Cite
|
Sign up to set email alerts
|

Transposable element expansion and low-level piRNA silencing in grasshoppers may cause genome gigantism

Abstract: Background Transposable elements (TEs) have been likened to parasites in the genome that reproduce and move ceaselessly in the host, continuously enlarging the host genome. However, the Piwi-interacting RNA (piRNA) pathway defends animal genomes against the harmful consequences of TE invasion by imposing small-RNA-mediated silencing. Here we compare the TE activity of two grasshopper species with different genome sizes in Acrididae (Locusta migratoria manilensis♀1C = 6.60 pg, Angaracris rhodopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 137 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…While the current study includes assembly lengths up to 4100 Mb, flow cytometry data shows evidence of insect genomes exceeding 18,000 Mb ( Bryodemella holdereri , Cong et al 2022). Insect models have potential to offer new insights on genome gigantism as assemblies for additional large-genome species become available (Liu et al 2022). With high species diversity and broad distributions in nearly all habitat types, insects may be particularly useful for understanding factors driving temporal dynamics of TE activity including population demographics (Schrader et al 2014) and environmental stress (Horváth et al 2017; Signor et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While the current study includes assembly lengths up to 4100 Mb, flow cytometry data shows evidence of insect genomes exceeding 18,000 Mb ( Bryodemella holdereri , Cong et al 2022). Insect models have potential to offer new insights on genome gigantism as assemblies for additional large-genome species become available (Liu et al 2022). With high species diversity and broad distributions in nearly all habitat types, insects may be particularly useful for understanding factors driving temporal dynamics of TE activity including population demographics (Schrader et al 2014) and environmental stress (Horváth et al 2017; Signor et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies in invertebrates have begun to reveal differences in TE and silencing dynamics in genomes of different sizes. In a pairwise comparison of grasshopper species with different genome sizes, Liu et al revealed that the species with the larger genome had higher TE expression, lower piRNA abundance, and lower expression of the piRNA biogenesis gene HENMT, which suggested that lower piRNA-mediated TE silencing was permissive to higher TE activity and genome expansion (Liu et al, 2022). A comparison between Drosophila melanogaster and the mosquito Aedes aegypti, which has a larger genome (1.38 Gb versus 180 Mb), revealed that the mosquito has a higher TE load and a smaller percentage of TEmapping piRNAs (Arensburger et al, 2011).…”
Section: The Te-silencing Arms Race Dynamic Across Genome Sizesmentioning
confidence: 99%
“…A few studies in invertebrates have begun to reveal differences in TE and silencing dynamics in genomes of different sizes. In a pairwise comparison of grasshopper species with different genome sizes, Liu et al revealed that the species with the larger genome had higher TE expression, lower piRNA abundance, and lower expression of the piRNA biogenesis gene HENMT , which suggested that lower piRNA-mediated TE silencing was permissive to higher TE activity and genome expansion (Liu et al, 2022). A comparison between Drosophila melanogaster and the mosquito Aedes aegypti , which has a larger genome (1.38 Gb versus 180 Mb), revealed that the mosquito has a higher TE load and a smaller percentage of TE-mapping piRNAs (Arensburger et al, 2011).…”
Section: Discussionmentioning
confidence: 99%